2018
DOI: 10.1007/s40843-017-9221-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotating magnetic field-controlled fabrication of magnetic hydrogel with spatially disk-like microstructures

Abstract: Composite biomaterials with controllable microstructures play an increasingly important role in tissue engineering and regenerative medicine. Here, we report a magnetic hydrogel composite with disk-like microstructure fabricated by assembly of iron oxide nanoparticles during the gelation process in the presence of rotating magnetic field. It should be mentioned that the iron oxide nanoparticles here were synthesized identically following techniques of Ferumoxytol that is the only inorganic nanodrug approved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The control of the surface morphology in hydrogels has a potential impact on the development of high-performance devices for biomedical applications, such as tissueengineered scaffolds and systems for drug delivery. Noting that surface morphology provides a unique way of controlling cell-biomaterial interaction and plays a major role in modulating cellular behaviour, such as cell attachment and proliferation during cell culture [46][47][48]. We found that by precisely varying the rotation speed of the VFD tube, PVA hydrogel films with different surface morphologies were readily fabricated.…”
Section: Resultsmentioning
confidence: 96%
“…The control of the surface morphology in hydrogels has a potential impact on the development of high-performance devices for biomedical applications, such as tissueengineered scaffolds and systems for drug delivery. Noting that surface morphology provides a unique way of controlling cell-biomaterial interaction and plays a major role in modulating cellular behaviour, such as cell attachment and proliferation during cell culture [46][47][48]. We found that by precisely varying the rotation speed of the VFD tube, PVA hydrogel films with different surface morphologies were readily fabricated.…”
Section: Resultsmentioning
confidence: 96%
“…The nanoparticles can form head-to-tail structures to minimize the systematic energy [114]. In particular, the rotating magnetic field composed of two magnets fixed on a motor can result in the formation of disk-like assemblies of magnetic nanoparticles [116]. The process of assembly might be attributed to the coupled interaction of magnetic dipolar force, a torsional force from the rotation field and viscous resistance from the fluid.…”
Section: External Magnetic Field-assisted Assembly Of Mnpsmentioning
confidence: 99%
“…For instance, the nanomaterial's overall particle size must be significantly small to avoid being engulfed by the reticuloendothelial system (RES), a vital nonspecific immune system formed by macrophages residing in tissues and relatively large to avoid kidney clearance. Besides, proper surface modification can reduce the magnetic nanomaterials' surface toxicity and enable them to be enriched in specific regions, a prerequisite in tumor diagnosis and targeted therapy [32]. Furthermore, the appropriate nanomaterials' surface modification exhibits precision characteristics when coated with targeting ligands such as proteins, peptides, antibodies, or other small molecules.…”
Section: Surface Modification Of Magnetic Nanomaterialsmentioning
confidence: 99%